Long-term meteor wind observations as by-products of routine measurements of PANSY radar at Syowa St. (69S), Antarctica - Tsutsumi, Masaki; Hashimoto, Taishi; Nishimura, Koji; Sato, Toru; Kohma, Masashi; Sato, Kaoru (2023)
The 14th Symposium on Polar Science/Interdisciplinary sessions [IW] Whole Atmosphere, Thu. 16 Nov. / 3F Multipurpose Conference room, Institute of Statistical Mathematics conference object